PELATIHAN LITERASI BACA TULIS DAN NUMERASI DASAR BAGI ANAK-ANAK KELUARGA PRA-SEJAHTERA DI WILAYAH KALIACAI, KELURAHAN VIM, KOTARAJA JAYAPURA - Johnson Siallagan; Agnes Eri Maryuni; Natasha Sihite (LPPM Uncen, 2020)
The unability in reading, writing and counting of the elementary school students will become a serious problem, facing the more complex lesson. The purpose of this activity was to provide a short training of student about reading, writing and numeration literacy. The participants were children came from weak economic family, class 1 to 3 of the elementary school. Observation before and after training prove that the learning process, using variation method, was able to improve the student competency in reading, writing and counting. Keywords: reading, writing, numeration literacy, elementary school